2011
DOI: 10.1021/cm1032404
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled and Cross-Linked Fullerene Interlayer on Titanium Oxide for Highly Efficient Inverted Polymer Solar Cells

Abstract: b S Supporting Information ' INTRODUCTIONPolymeric solar cells (PSCs) have emerged as a promising alternative technique for producing clean and renewable energy due to their potential for fabrication onto large areas of lightweight flexible substrates by low-cost solution processing. To maximize the donor-acceptor heterojunction interfacial area for efficient exciton dissociation, mainstream PSC devices adopt the concept of a bulk heterojunction (BHJ), where an active layer contains a p-type donor and an n-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 40 publications
2
53
0
2
Order By: Relevance
“…The authors showed that with appropriate choice of SOMs, the device performance of the PSCs can be improved dramatically. Later, Cheng et al [43] reported the synthesis of two oxetane-functionalized cross-linked fullerene derivatives that can form self-assembling layer on the surface of TiOx for inverted type PSCs. It is worth noting that these cross-linked fullerene derivatives can effectively prevent the consequent interfacial erosion, and thus are ideal for the fabrication of all-solution processing PSCs.…”
Section: Self-organized Cathode Interfacial Layer Materialsmentioning
confidence: 99%
“…The authors showed that with appropriate choice of SOMs, the device performance of the PSCs can be improved dramatically. Later, Cheng et al [43] reported the synthesis of two oxetane-functionalized cross-linked fullerene derivatives that can form self-assembling layer on the surface of TiOx for inverted type PSCs. It is worth noting that these cross-linked fullerene derivatives can effectively prevent the consequent interfacial erosion, and thus are ideal for the fabrication of all-solution processing PSCs.…”
Section: Self-organized Cathode Interfacial Layer Materialsmentioning
confidence: 99%
“…[7][8][9][10] Therefore, we finally measured the WFs of the ITO substrate, neat ZnO, and d-ZnO by using ultraviolet photoelectron spectroscopy (UPS), as shown in Figure S8 in the Supporting Information. [7][8][9][10] Therefore, we finally measured the WFs of the ITO substrate, neat ZnO, and d-ZnO by using ultraviolet photoelectron spectroscopy (UPS), as shown in Figure S8 in the Supporting Information.…”
Section: Improved Energy Level Alignment At the Cathodementioning
confidence: 99%
“…It is well known that the presence of buffer layers in PSCs affects the WF of electrodes, and thus, provides the ohmic contact at electrodes. [7][8][9][10] Therefore, we finally measured the WFs of the ITO substrate, neat ZnO, and d-ZnO by using ultraviolet photoelectron spectroscopy (UPS), as shown in Figure S8 in the Supporting Information. The WF values of ITO, neat ZnO, and d-ZnO were calculated to be about 4.7, 4.5, and 4.4 eV, respectively.…”
Section: Improved Energy Level Alignment At the Cathodementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is evidence in the literature that oxetane crosslinking is possible in the presence of fullerenes. 18 The first low-bandgap polymer we have chosen is poly(2,7-(9-(2'-ethylhexyl)-9-hexylfluorene)-alt-5,5-(4',7'-di-3-hexylthien-2-yl-2',1',3'-benzothiadiazole) PFDTBT first synthesized by Svensson et al in 2003. 19 The high mobility and stability of polyfluorene in combination with the benzothiadiazole comonomer DTBT that lowers the bandgap of the polymer render PFDTBT suitable for the use in organic solar cells and lead to a device efficiency of 2.2%.…”
Section: Synthesis Of Photocrosslinkable Low-bandgap Polymersmentioning
confidence: 99%